2008
DOI: 10.3171/foc/2008/25/9/e11
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for medically refractory epilepsy

Abstract: Epilepsy is a chronic neurological disorder that affects 0.5–1% of the population. Up to one-third of patients will have incompletely controlled seizures or debilitating side effects of anticonvulsant medications. Although some of these patients may be candidates for resection, many are not. The desire to find alternative treatments for epilepsy has led to a resurgence of interest in the use of deep brain stimulation (DBS), which has been used quite successfully in movement disorders. Small pilot studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 88 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…The vast majority of the animal experimental studies but also the clinical trials have used the cerebellum cortical surface as stimulation target, with frequently contradictory results. 8,5,[14][15][16]22,23,38,48,52,53 However, the stimulation of the deep cerebellar nuclei appears to provide more solid data and better seizure control. 1,35 There are several mechanisms that may explain this discrepancy in the results of the cortical CS in animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the animal experimental studies but also the clinical trials have used the cerebellum cortical surface as stimulation target, with frequently contradictory results. 8,5,[14][15][16]22,23,38,48,52,53 However, the stimulation of the deep cerebellar nuclei appears to provide more solid data and better seizure control. 1,35 There are several mechanisms that may explain this discrepancy in the results of the cortical CS in animal and human studies.…”
Section: Discussionmentioning
confidence: 99%
“…9,29,40,61 The output of the cerebellum to the ascending reticular formation may be implicated in the inhibitory effect of the cerebellum to the basal ganglia neuronal network, which results in decreased activity of the excitatory thalamocortical projections. 9,16 This process ultimately results in inhibition of cortical excitability. There is a wide variation in the animal models used, the seizure induction methodology, the exact stimulation target, the stimulation methodology, and the stimulation parameters.…”
Section: Animal Experimental Studiesmentioning
confidence: 99%
“…Although larger than most other DBS targets, and therefore potentially more prone to targeting error and variability, the hippocampus is often stereotactically accessed with recording electrodes and consequently is a relatively familiar target for epilepsy surgeons. Several studies of hippocampal slices and rodent models provided preclinical support for hippocampal DBS [22,36,58,59]. The first systematic human studies of hippocampal stimulation came from Velasco and colleagues, initially in a pilot study of stimulation prior to temporal lobectomy in 10 patients [27].…”
Section: Hippocampal Formationmentioning
confidence: 99%
“…Among the most common targets investigated in adult DBS studies are the hippocampus, subthalamic nucleus, and thalamus. 14,19 Among these studies, Velasco et al 48 demonstrated that hippocampal stimulation reduced interictal spikes as well as the frequency of complex partial and tonic-clonic seizures in patients with medically refractory temporal lobe epilepsy. Benabid et al 5 treated a child with inoperable cortical dysplasia and refractory epilepsy with subthalamic nucleus DBS and observed an 83% improvement in seizure frequency as well as improvement of motor function.…”
Section: Epilepsymentioning
confidence: 99%